WAYS OF METHODOLOGICAL PREPARATION OF PRIMARY SCHOOL TEACHERS FOR FLIPPED LEARNING TECHNOLOGY - Ibragimov A’lamjon Amrilloyevich; Hamidova Laylo Kamildjonovna (Research Focus International Scientific Journal, 2025)
This article explores the ways of methodological preparation of primary school teachers for the use of flipped learning technology. It analyzes the essence of flipped learning, its advantages, and the possibilities of applying this approach in the primary education process. Special attention is given to developing prospective teachers’ abilities for independent learning, the practical application of innovative technologies, and the effective use of interactive methods. The research findings contribute to enhancing the methodological readiness of primary school teachers in accordance with the requirements of modern education.